2016
DOI: 10.1158/2159-8290.cd-16-0050
|View full text |Cite
|
Sign up to set email alerts
|

Phase IB Study of Vemurafenib in Combination with Irinotecan and Cetuximab in Patients with Metastatic Colorectal Cancer with BRAFV600E Mutation

Abstract: In vitro, EGFR inhibition, combined with the BRAF inhibitor vemurafenib, causes synergistic cytotoxicity for BRAFV600E metastatic colorectal cancer (mCRC), further augmented by irinotecan. The safety and efficacy of vemurafenib, irinotecan, and cetuximab in BRAF-mutated malignancies are not defined. In this 3+3 phase I study, patients with BRAFV600E advanced solid cancers received cetuximab and irinotecan with escalating doses of vemurafenib. Nineteen patients (18 with mCRC, 1 with appendiceal cancer) were enr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
145
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 199 publications
(173 citation statements)
references
References 31 publications
(34 reference statements)
6
145
0
4
Order By: Relevance
“…These results suggest that mutation clonality, as it exists in tumor tissue, can be estimated from properly normalized relative cfDNA VAFs, as has been previously hypothesized (28). High accuracy in VAF estimation is likely key to the success of this approach, and notably, VAFs measured by the cfDNA NGS assay used in this study show good agreement with digital droplet PCR (29,30). This approach points to the possibility of analyzing the clonal structures of tumors from cfDNA sequencing data, unencumbered by the complications of tumor heterogeneity and tumor impurity introduced by single-region tissue sampling.…”
Section: Discussionsupporting
confidence: 77%
“…These results suggest that mutation clonality, as it exists in tumor tissue, can be estimated from properly normalized relative cfDNA VAFs, as has been previously hypothesized (28). High accuracy in VAF estimation is likely key to the success of this approach, and notably, VAFs measured by the cfDNA NGS assay used in this study show good agreement with digital droplet PCR (29,30). This approach points to the possibility of analyzing the clonal structures of tumors from cfDNA sequencing data, unencumbered by the complications of tumor heterogeneity and tumor impurity introduced by single-region tissue sampling.…”
Section: Discussionsupporting
confidence: 77%
“…However, the prognostic information might guide other clinical decisions. To improve outcomes for these patients, recent studies have evaluated feasibility of treatment with anti-EGFR antibodies and other targeted agents (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…This phase I study of the BRAF inhibitor LGX818 in combination with cetuximab, with or without the PIK3CA inhibitor BYL719, in advanced BRAF-mutated and KRAS wild-type colorectal cancer patients reported no complete responses but 7 ($30%) partial responses from the dual combination of LGX818 with cetuximab and 6 ($30%) partial responses from the triple combination of LGX818, cetuximab, and BYL719 (81). Finally, preliminary results from a phase Ib trial of vemurafenib in combination with irinotecan and cetuximab in BRAFmutated advanced cancers and colorectal cancer patients reported that 6 of 17 evaluable BRAF V600E-mutated colorectal cancer patients achieved a partial response Hong and colleagues (82).…”
Section: Role Of Egfrmentioning
confidence: 99%